Bentuk-Bentuk Hegemoni pada Tokoh Periferal dalam Novel “Pasung Jiwa” Karya Okky Madasari - Maria Benga Geleuk (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to explain the forms of power experienced by peripheral characters in the Pasung Jiwa novel by Okky Madasari. In addition, this study also explains the strategies carried out by these three peripheral characters to fight systemic power in the midst of society. In terms of analyzing existing problems, this research uses the theory of Hegemony from Antonio Gramsci through descriptive qualitative methods using the sociology of literary works, namely using forms of power that have been developed on the three characters in the story. The results showed the difference between humans in getting freedom in the period before and after the reform. This novel shows the existence of hegemony that occurs in several peripheral characters in the story, namely Sasana, Cak Jek, and Elis. In the process of searching for identity, the three of them found what was done by the family, even in religious organizations. These forms of hegemony also dominate their bodies and minds. Sasana, Cak Jek, and Elis are aware that its domination does not only occur in themselves, but also in the whole society. Therefore, these three characters choose to fight the hegemony that experienced in themselves with the struggle to make themselves free from the systemic power, both from the confinement family, the norms that exist in society, work, and also the doctrines of religion that have already dominated Sasana, Cak Jek, and Elis.